Assessment Models for Predicting Economic Situation of Small and Medium Enterprises – Multicriteria Analysis - Burda, Andrzej (Regional Barometer. Analyses & Prognoses, 2009)
This paper proposes a way of evaluation of the models for predicting economic and financial situation of small and medium-sized enterprises. The advantages and disadvantages of the machine learning and statistical models were analyzed by using accepted criteria. It proposes the concept of optimization of heterogeneous predicting model.